2021
DOI: 10.1186/s12915-021-01012-5
|View full text |Cite
|
Sign up to set email alerts
|

Natural abundance isotope ratios to differentiate sources of carbon used during tumor growth in vivo

Abstract: Background Radioactive or stable isotopic labeling of metabolites is a strategy that is routinely used to map the cellular fate of a selected labeled metabolite after it is added to cell culture or to the circulation of an animal. However, a labeled metabolite can be enzymatically changed in cellular metabolism, complicating the use of this experimental strategy to understand how a labeled metabolite moves between organs. These methods are also technically demanding, expensive and potentially t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“… Sources of carbon incorporated into tumor biomass were differentiated by changing the isotopic carbon content of the food source 25 h before measuring the total carbon content and isotopic ratio of the tumor. A similar, but independent experiment is reported in Holland et al ( 2021 ). …”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“… Sources of carbon incorporated into tumor biomass were differentiated by changing the isotopic carbon content of the food source 25 h before measuring the total carbon content and isotopic ratio of the tumor. A similar, but independent experiment is reported in Holland et al ( 2021 ). …”
Section: Resultssupporting
confidence: 83%
“…To test this hypothesis, we sought to differentiate whether biomass of the growing tumor was derived from ingested food or nutrients released from host organ stores. As both sugars and amino acids were mobilized as a group, we chose to follow transfer of carbon using natural abundance stable isotope ratio mass spectrometry (SIRMS) using a recently developed protocol (Holland et al , 2021 ). We generated two types of fly food containing different 13 C/ 12 C ratios derived from plants with differences in 13 C vs. 12 C incorporation from CO 2 during photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently described stable carbon isotope tracing technique has allowed to distinguish whether tumor biomass is derived from food or host tissues. Using this technique, it was demonstrated that Ras V12 ; scrib −/− larval tumors first grow mainly on nutrients from food and progressively incorporates more nutrients from host tissues [115,140]. Autophagy is aberrantly activated in muscles and fat body of Ras V12 ; scrib −/− tumor-bearing larvae suggesting that wasted organs might provide nutrients to the tumor through "organ self-digestion" [54].…”
Section: Organ Wasting Feeds the Tumormentioning
confidence: 99%